2015
DOI: 10.2337/db15-0242
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of NF-κB p65 (RelA) in Liver Improves Insulin Sensitivity and Inhibits cAMP/PKA Pathway

Abstract: The transcription factor nuclear factor-κB (NF-κB) mediates inflammation and stress signals in cells. To test NF-κB in the control of hepatic insulin sensitivity, we inactivated NF-κB in the livers of C57BL/6 mice through deletion of the p65 gene, which was achieved by crossing floxed-p65 and Alb-cre mice to generate L-p65-knockout (KO) mice. KO mice did not exhibit any alterations in growth, reproduction, and body weight while on a chow diet. However, the mice on a high-fat diet (HFD) exhibited an improvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 30 publications
6
69
0
Order By: Relevance
“…35,36 SQSTM1 encodes a multifunctional protein that besides binding ubiquitin and regulating activation of the nuclear factor kappa-B (NF-kB) signaling pathway, has also effects related to impairment of autophagic flux, 37 thereby contributing to hepatic insulin sensitivity. [38][39][40] Moreover, correlations of NASH-associated CpG sites with mRNA expression of CEACAM1, SH3BP4 (encoding transferrin receptor-trafficking protein), and NAT2 also support a role for our findings relating differential DNA methylation in NASH with impaired insulin signaling/action. [41][42][43][44][45][46][47] The mechanisms that could alter DNA methylation in the insulin-resistant liver remain to be elucidated.…”
Section: Discussionmentioning
confidence: 49%
“…35,36 SQSTM1 encodes a multifunctional protein that besides binding ubiquitin and regulating activation of the nuclear factor kappa-B (NF-kB) signaling pathway, has also effects related to impairment of autophagic flux, 37 thereby contributing to hepatic insulin sensitivity. [38][39][40] Moreover, correlations of NASH-associated CpG sites with mRNA expression of CEACAM1, SH3BP4 (encoding transferrin receptor-trafficking protein), and NAT2 also support a role for our findings relating differential DNA methylation in NASH with impaired insulin signaling/action. [41][42][43][44][45][46][47] The mechanisms that could alter DNA methylation in the insulin-resistant liver remain to be elucidated.…”
Section: Discussionmentioning
confidence: 49%
“…Moreover, a recent study has shown that hepatic AMPK can phosphorylate and activate PDE4B to suppress glucagon-mediated cAMP/PKA activation (Johanns et al 2016), suggesting that metformin inhibits hepatic PKA via multiple pathways. Another study showed that selective inactivation of NF-κB in mouse liver enhanced insulin sensitivity and suppressed hepatic gluconeogenesis also via inhibition of the cAMP/PKA/CREB pathway (Ke et al 2015). These studies suggest that cAMP/PKA is the major positive regulator for hepatic gluconeogenesis.…”
Section: Camp/pka In the Livermentioning
confidence: 94%
“…Several PDE subtypes and isoforms, including PDE1 [7], PDE3B [8,9], PDE4 [7] and PDE8B [7,10], are known to mediate insulin secretion by pancreatic islets and/or beta cells. Through a feedback mechanism, insulin can reduce intracellular cAMP levels via activation of PDEs either by phosphorylation [11,12] or in the longer term by regulating their protein levels [13,14].…”
Section: Introductionmentioning
confidence: 99%